THE EFFECTIVENESS OF USING THINK PAIR SHARE (TPS) AND JIGSAW COOPERATIVE MODELS IN MATHEMATICS LEARNING ON PROBLEM SOLVING ABILITY IN CLASS VII SMP - Anis Dyah Fitriyani; Abdul Taram (Universitas Ahmad Dahlan, 2019)
Common student problem-solving ability is related to several factors. The use of cooperative models in learning is one of the possible factors that can improve student problem-solving abilities. This study aims to determine the effectiveness of using the think pair share cooperative model and the cooperative jigsaw model on seventh-grade students' problem-solving ability of the odd semester of SMP Negeri 1 Tembarak in 2018/2019 academic year. The research population consisted of class VII students of SMP Negeri 1 Tembarak in the odd semester of the 2018/2019 academic year, which consisted of classes VII A, VII B, VII C, VII D, VII E, VII D, VII F, totaling 169 students. Samples were taken from class VII A as the first experimental class using the think pair share cooperative model and class VII D as the second experiment class using the jigsaw cooperative jigsaw techniques using essay questions to obtain data on students' problem-solving abilities. The research instrument test includes a validation test, reliability test, difference power test. The analysis prerequisite test includes the normality test, homogeneity test, initial ability test, hypothesis test. The results showed differences in students' problem-solving abilities who used the think pair share cooperative model using the cooperative jigsaw model. This is indicated by then rejected received. From the research results, students' problem-solving ability using the cooperative model, think pair share, is higher than using the cooperative jigsaw model. This is indicated by then rejected received.